2021
DOI: 10.3389/fgene.2021.659788
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Associated Co-expression Network Identifies Novel Biomarkers for Digestive System Cancer

Abstract: Cancers of the digestive system are malignant diseases. Our study focused on colon cancer, esophageal cancer (ESCC), rectal cancer, gastric cancer (GC), and rectosigmoid junction cancer to identify possible biomarkers for these diseases. The transcriptome data were downloaded from the TCGA database (The Cancer Genome Atlas Program), and a network was constructed using the WGCNA algorithm. Two significant modules were found, and coexpression networks were constructed. CytoHubba was used to identify hub genes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Xianzheng Qin et al revealed that hsa-miR-26a-5p can be used as a potential prognostic biomarker for patients with intrahepatic cholangiocarcinoma (30). Moreover, hsa-miR-26a-5p was proposed to be associated with the prognosis of gastrointestinal tumors by Zheng Chen et al (31). However, there are no relevant reports on the functional and mechanistic roles of AL513318.2 until now.…”
Section: Discussionmentioning
confidence: 99%
“…Xianzheng Qin et al revealed that hsa-miR-26a-5p can be used as a potential prognostic biomarker for patients with intrahepatic cholangiocarcinoma (30). Moreover, hsa-miR-26a-5p was proposed to be associated with the prognosis of gastrointestinal tumors by Zheng Chen et al (31). However, there are no relevant reports on the functional and mechanistic roles of AL513318.2 until now.…”
Section: Discussionmentioning
confidence: 99%
“…Protein digestion and absorption have been consistently found to be involved in digestive system cancers from RNA-sequencing studies. 37 However, it has been identified in gallbladder cancer for the first time, including the FXYD2 and the Collagen family. Collagen is the major component of the tumor microenvironment and participates in cancer fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the remnant miRNAs, one study suggested opposite effects from what we have reported for hsa-miR-181a-2-3p in glioblastoma [ 54 ], and two studies found hsa-miR-331-3p to be under-expressed in prostate cancers [ 55 ] and CRC [ 56 ] compared to healthy groups. Higher levels of hsa-29b-2-5p expression were associated with the staging of esophageal and gastric cancer [ 57 ] in TCGA. However, this association was not observed in TCGA COAD stage II samples.…”
Section: Discussionmentioning
confidence: 99%